Structure, Morphology and Opto-Electrical Properties of Nanostructured Indium Doped SnO2 Thin Films Deposited by Thermal Evaporation - Md. Mahafuzur Rahaman; Kazi Md. Amjad Hussain; Mehnaz Sharmin; Chitra Das; Shamima Choudhury (European Scientific Journal, ESJ, 2016)
Indium doped Tin oxide (SnO2: In) thin films of various thicknesses (200-600 nm) with fixed 2% indium (In) concentration were prepared by thermal evaporation method onto glass substrates under high vacuum (10-6 Torr). As deposited films were vacuum annealed at 200o C for 60 minutes. The structure, optical, electrical and morphology properties of SnO2: In thin films were investigated as a function of film thickness. The XRD analysis revealed that films were polycrystalline in nature with a tetragonal structure having (110) plane as the preferred orientation. The average crystalline size increased from 34.8 to 51.25 nm with increase of film thicknesses. The surface morphology of the doped films was obtained by Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscope (FESEM). Optical transmittance was obtained from a double beam UV-Vis- NIR spectrophotometer. Maximum transmittance varied from 65-76% in the visible range of the spectrum. Optical band gap (Eg) varied between 2.89 and 3.20 eV. The resistivity of SnO2: In thin films was as high as 105 Ω-cm. Activation energy of the films were found to be 0.18 to 0.47 eV for 300-600 nm film thicknesses. Due to high optical band gap and high electrical resistivity, these nanostructured films can be used in optoelectronic devices especially as opto-insulator.